Headache Perception in an Epilepsy Patient with Neuromodulation by Anterior Thalamic Nuclei Deep Brain Stimulation: A Case Report - Pintea, Bogdan; Surges, Rainer; Boström, Jan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Objective Headache disorders are frequently associated with epilepsy. Some neuromodulation techniques for refractory epilepsy have been reported to positively influence the associated chronic headache. However, the exact mechanism of action of vagus nerve stimulation (VNS) and anterior thalamic nuclei-deep brain stimulation (ANT-DBS) on pain perception is unclear.Method We report a structured assessment of pain perception in a patient who experienced headache relief after ANT-DBS for refractory focal epilepsy and compare it with pain perception of epilepsy patients with chronic headache who were treated with and without VNS.Results The pain-associated symptoms in the ANT-DBS case were on the Pain Anxiety Symptoms Scale (PASS-40) subscore “physiological anxiety” closer to the control collective, whereas in patients with VNS, this was more likely for the PASS-40 subscores “cognitive anxiety” or “escape and avoidance.”Conclusion ANT-DBS and VNS may influence epilepsy-associated chronic headache in different ways.
Keywords: ANT-DBS; migraine; pain perception; VNS; epilepsy